2017
DOI: 10.1136/bmjopen-2016-015420
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of melatonin for prevention of delirium in critically ill patients: a protocol for a multicentre, randomised, placebo-controlled study

Abstract: IntroductionDelirium is highly prevalent in the intensive care unit (ICU) and is associated with adverse clinical outcomes. At this time, there is no drug that effectively prevents delirium in critically ill patients. Alterations in melatonin secretion and metabolism may contribute to the development of delirium. Administration of exogenous melatonin has been shown to prevent delirium in non-critically ill surgical and medical patients. This trial will demonstrate the feasibility of a planned multicentre, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It has been suggested that exogenous melatonin administration may play an important role as a prophylactic agent in preventing delirium in the critically ill patients. This hypothesis is actually explored in two randomized and controlled trials, that use melatonin in standard formulation administered orally or via nasogastric tube. Given the growing interest in the use of melatonin in ICU patients, it may be important to find the optimal formulation, delivery route and dosage schedule capable of mimicking the endogenous secretion pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that exogenous melatonin administration may play an important role as a prophylactic agent in preventing delirium in the critically ill patients. This hypothesis is actually explored in two randomized and controlled trials, that use melatonin in standard formulation administered orally or via nasogastric tube. Given the growing interest in the use of melatonin in ICU patients, it may be important to find the optimal formulation, delivery route and dosage schedule capable of mimicking the endogenous secretion pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Future RCTs will need to include well-validated tools to identify delirium and ensure they are adequately powered to identify between-group differences. A number of published study protocols ( 59 , 60 ), including feasibility studies ( 61 , 62 ), suggest that such improvements in the available evidence of the efficacy of melatonin analogs to prevent delirium are forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is therefore needed. Based on available data, potentially effective interventions might include a combination of dexmedetomidine ( 62 ), oral melatonin ( 95 ), and cognitive behavioral sleep therapy ( 96 ) using modified polysomnography to quantify sleep quality and quantity ( 25 , 78 ) and understand to which extent sleep actually affects delirium occurrence.…”
Section: Strategies To Improve Sleep and Realign Circadian Rhythm In mentioning
confidence: 99%